Metallothionein 2 regulates endothelial cell migration through transcriptional regulation of vegfc expression - Schuermann, Annika (Angiogenesis, 2015)
Analysis of developmental angiogenesis can help to identify regulatory networks, which also contribute to disease-related vascular growth. Vascular endothelial growth factors (Vegf) drive angiogenic processes such as sprouting, endothelial cell (EC) migration and proliferation. However, how Vegf expression is regulated during development is not well understood. By analyzing developmental zebrafish angiogenesis, we have identified Metallothionein 2 (Mt2) as a novel regulator of vegfc expression. While Metallothioneins (Mts) have been extensively analyzed for their capability of regulating homeostasis and metal detoxification, we demonstrate that Mt2 is required for EC migration, proliferation and angiogenic sprouting upstream of vegfc expression. We further demonstrate that another Mt family member cannot compensate Mt2 deficiency and therefore postulate that Mt2 regulates angiogenesis independent of its canonical Mt function. Our data not only reveal a non-canonical function of Mt2 in angiogenesis, but also propose Mt2 as a novel regulator of vegfc expression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10456-015-9473-6) contains supplementary material, which is available to authorized users.